The Role of Organizational Commitment Mediation on Turnover Intention of Private Bank Employees - Astrid Rahayu; Abdul Haeba Ramli; Siti Mariam; Kusnadi Kusnadi; Dennish Tablante (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The banking industry in Indonesia has to contend with constantly shifting obstacles in order to retain top talent. The stability of the business and the return on investments in human capital development are both adversely affected by high staff turnover rates. The purpose of this study is to examine how organizational commitment mediates the relationship between leadership, turnover intention, and human resource development among Tangerang private bank workers. Understanding the factors that determine the high degree of turnover intention in the banking industry is crucial since it can negatively affect organizational stability. 190 individuals participated in an online survey that collected data for this study, which used quantitative methodologies. Using SmartPLS, structural equation modeling (SEM) was used to analyze the data. The findings demonstrated that, either directly or indirectly, human resource development has no discernible impact on organizational commitment or turnover intention. On the other hand, leadership significantly lowers turnover intention. The study's findings highlight how crucial it is to train leaders effectively in order to increase staff retention. Organizations must also establish a healthy work environment and strike a balance between employees' personal and professional lives in order to increase their loyalty to the business. The findings of this study add to the body of knowledge on the variables influencing turnover intention and help managers create human resource management plans that are more successful. Keywords: Organizational Commitment, Human Resource Development, Leadership, Turnover Intention.